Banking Financial Performance: Mitigation Forms, Efficiency, Capabilities and Debt - Edy Jumady, Bungatang, (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
This study aims to examine how the Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (OEOI), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) affect the profitability of Return on Assets (ROA). The object of this research is that conventional commercial banks are chosen because they have a relatively rapid growth compared to Islamic commercial banks. This type of research includes causal research using quantitative methods. The population of this study is banking companies registered in the Indonesia Banking Directory and the 2018-2020 Bank Indonesia monthly publication reports. Sampling used the saturated sample method, with 36 data samples from the 2018-2020 Bank Indonesia Monthly Published Reports. Then the data were analyzed using multiple linear regression analysis with the Ordinary Least Square model using the Eviews Version 12 software. The data test results found that the Capital Adequacy Ratio (CAR) had no significant effect on profitability. Meanwhile, Operating Expenses Operating Income (OEOI), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) have a positive and significant effect on profitability.